2015
DOI: 10.1186/s40001-015-0190-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral reactivity in migraine patients measured with functional near-infrared spectroscopy

Abstract: BackgroundThere are two major theories describing the pathophysiology of migraines. Vascular theory explains that migraines resulted from vasodilation of meningeal vessels irritating the trigeminal nerves and causing pain. More recently, a neural theory of migraine has been proposed, which suggests that cortical hyperexcitability leads to cortical spreading depression (CSD) causing migraine-like symptoms. Chronic migraine requires prophylactic therapy. When oral agents fail, there are several intravenous agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Several isoforms of O 2 •− -producing NADPH oxidase exists in the vascular wall [ 60 ]. Many types of vascular diseases appear as being associated with the up-regulation of NADPH oxidase [ 57 ] and evidence suggested that migraine pathophysiology is connected with vascular reactivity [ 61 , 62 ]. Endothelial NOS (eNOS) appears mainly involved in migraine pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Several isoforms of O 2 •− -producing NADPH oxidase exists in the vascular wall [ 60 ]. Many types of vascular diseases appear as being associated with the up-regulation of NADPH oxidase [ 57 ] and evidence suggested that migraine pathophysiology is connected with vascular reactivity [ 61 , 62 ]. Endothelial NOS (eNOS) appears mainly involved in migraine pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Functional NIRS can be a potential biomarker to assess treatment responses to medication in patients with migraine. A more recent study has shown differences in hemodynamic changes between patients who received valproic acid, magnesium sulfate and dihydroergotamine suggesting their distinctive mechanisms for migraine treatment (Pourshoghi et al, 2015). In the next subsection, the potential of fNIRS as a diagnostic biomarker is further illustrated in mild cognitive impairment.…”
Section: Migrainementioning
confidence: 94%
“…Alternatively, functional near-infrared spectroscopy (fNIRS) has recently been suggested for monitoring cortical hemodynamic response to experimentally and clinically induced acute pain in adults and infants. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] fNIRS is an optical imaging tool for noninvasive, continuous monitoring of regional blood flow and tissue oxygenation. [29][30][31] This imaging technique offers several advantages over other hemodynamic-based imaging techniques including being portable and noninvasive, no ionizing radiation or drug injection, measuring two hemodynamic parameters-deoxyhemoglobin (HHb) and oxyhemoglobin (HbO 2 )-simultaneously, and relative robustness to motion artifact, which is desirable for the study of infants, small children, or elders with involuntary movement disorders.…”
Section: Introductionmentioning
confidence: 99%